Perceptions about diabetes and their disease in seniors and their families of an urban area of Costa Rica - Sedó Masís, Patricia (2011)
This study of perceptions study on Diabetes Mellitus (DM) was carried out in a group of elderly diabetics (PAMD) and their relatives of an urban area of Costa Rica. There was a predominant negative concept of the disease, and this was associated with a poor information and support from the family and health services. This negative concept favored poor self health care and disease control. The diagnosis is described as a crisis that causes sensations of dependency, negative changes in their daily life, feelings of hatred, resignation, without hope in terms of treatment and death; this diagnosis was found in both sexes and in all age groups. The situation combines with stereotyped vision of ageing with generates diverse feelings in the PAMD and their families, as they do not know how to act and their problems are not adequately detected. The perception of Diabetes Mellitus and the impact these have on the way the PAMD and their families think and act, demands the creation of policies and educational and assistance programs with an integral and gerontological pers- pective in order to counteract these stereotyped and negative visions and to produce changes in the way chronic health problems are dealt with at the individual, family, community and institutional levels in the search for a improved quality of life.